2022
DOI: 10.3389/fcell.2021.809955
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy, Pyroptosis, and Ferroptosis: New Regulatory Mechanisms for Atherosclerosis

Abstract: Atherosclerosis is a chronic inflammatory disorder characterized by the gradual buildup of plaques within the vessel wall of middle-sized and large arteries. The occurrence and development of atherosclerosis and the rupture of plaques are related to the injury of vascular cells, including endothelial cells, smooth muscle cells, and macrophages. Autophagy is a subcellular process that plays an important role in the degradation of proteins and damaged organelles, and the autophagy disorder of vascular cells is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 315 publications
0
39
0
1
Order By: Relevance
“…Different types of RCD occasionally share the same upstream molecules; accordingly, crosstalk between RCD pathways is inevitable. Ferroptosis is an iron-dependent form of RCD, and differs from apoptosis by excessive lipid peroxidation, lack of glutathione, and inactivation of caspase-3 (50,51). However, a recent study demonstrated that the ER stress-mediated CHOP-PUMA pathway was associated with the interaction between apoptosis and ferroptosis (52).…”
Section: Discussionmentioning
confidence: 99%
“…Different types of RCD occasionally share the same upstream molecules; accordingly, crosstalk between RCD pathways is inevitable. Ferroptosis is an iron-dependent form of RCD, and differs from apoptosis by excessive lipid peroxidation, lack of glutathione, and inactivation of caspase-3 (50,51). However, a recent study demonstrated that the ER stress-mediated CHOP-PUMA pathway was associated with the interaction between apoptosis and ferroptosis (52).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is characteristic by DNA fragmentation, destruction of the nuclear proteins and cytoskeleton, crosslinking of proteins, and the formation of apoptotic bodies [ 60 ]. Pyroptosis leads to cell swelling, pore formation, membrane rupture, and massive leakage of cytoplasmic components [ 61 ]. The links and mutual regulatory mechanisms between ferroptosis and other models of cell death are discussed below ( Figure 2 ).…”
Section: Ferroptosis and Other Cell Models Of Death After Tbimentioning
confidence: 99%
“…Under homeostatic conditions, these processes are used to remove damaged, infected, or mutated cells. However, in the context of ASCVD, loss of control over these processes can promote disease [ 29 ]. A highly regulated process for the clearance of dead cells, termed “efferocytosis,”, is another important aspect of inflammatory resolution and many studies show that enhancing efferocytosis can reduce plaque sizes in mouse models [ 30 ].…”
Section: Inflammation In Cardiovascular Diseasementioning
confidence: 99%